Review of protection aspects of microgrid devices - Ashoke Kumar Basu (International Journal of Advances in Applied Sciences, 2021)
A microgrid is required to provide reliable, quality and efficient supply of both electricity and heat demands to its customers when operates either in autonomous or in grid-connected modes. In this context, it is most important to address a comprehensive protection scheme of the microgrid suiting both the modes of operations. This paper concentrates on the impacts of various devices, like distributed energy resources (DERs), transformers, switches, microgrid topology, communication type, grounding type, to name a few, on the microgrid protection systems. The paper reviewes previous works for the various aspects, like characteristics, construction, of these devices in the light of protection. This review-work is useful for future research in the field of microgrid protection as well as in the selection of its devices.